Real Estate and Agricultural Wetlands in Kerala - P P Nikhil Raj, P A Azeez (Economic & Political Weekly EPW JANuary 31, 2009, 2009)
The "rice culture" of Kerala is fast vanishing due to the increasing diversion of the land for non-agricultural purposes. The real estate sector is gradually swallowing up the rice cultivating low-lying wetlands. This paper attempts to examine the growth of real estate business and consequent destruction of the wetland ecosystems in the state